Building National Character through the Classical Islamic Heritage: A Study of Character Education in Nashoihul ‘Ibad and Ta’lim al-Muta’allim - Fathurrohman, Asep; Syafe'i, Imam; Erlina, Erlina (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Character or morality holds a central position in Islam, as a person’s status in the sight of Allah is greatly influenced by their moral conduct. This study aims to describe the values of character education contained in the classical Islamic books Nashoihul 'Ibad and Ta’lim al-Muta'allim, and to explore their relevance to the goals of Islamic education in Indonesia. This research is a library study employing a qualitative approach. Data were collected through a literature review of various sources such as books, articles, and relevant journals, and were analyzed using documentation techniques and content analysis. The findings reveal that Nashoihul ‘Ibad contains character values such as piety (taqwa), wisdom, patience, asceticism (zuhud), humility (tawadhu), sincerity (ikhlas), justice, contentment (qana’ah), gratitude, and honesty. Meanwhile, Ta’lim al-Muta’allim emphasizes values such as patience, intelligence, diligence, gratitude, trust in God (tawakkul), compassion/tolerance, and prudence (wara’). These values reflect character traits in accordance with Islamic teachings and are highly relevant to the goals of Islamic education, namely to form individuals with noble character, based on the Qur’an and Sunnah, in pursuit of happiness in this world and the hereafter. This integrative comparative study of two foundational Islamic books provides a unique contribution to character education discourse by highlighting timeless moral values with practical relevance for Indonesian education. The core scientific contribution of this study lies in reviving classical Islamic values and positioning them meaningfully within the framework of contemporary Islamic education.